Тепловые эффекты полимеризации стирола; Научные труды SWORLD; Т. 26, № 1 - Ляпков А. А. Алексей Алексеевич; Ионова Е. И. Елена Ивановна; Бондалетов В. Г. Владимир Григорьевич; Шипилова Н. С. Наталья Сергеевна (2009, 2009)
Заглавие с экрана